Analisis Rasio Modal, Efisiensi Operasional, Bunga Bersih, Likuiditas, Dan Kredit Bermasalah, Terhadap Rasio Laba - Rahmat Rahmat; Endang Ruchiyat (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This study aims to analyze financial ratios which include Capital Ratios, Operational Efficiency Ratios, Net Interest Ratios, Liquidity Ratios, Non-Performing Loans Ratios to Profit Ratios at Conventional Commercial Banks in Indonesia. The banks studied were based on bank grouping in terms of ownership category which included State-Owned Banks, National Private Foreign Exchange Banks, National Private Non-Foreign Exchange Banks, Regional Development Banks, Joint Venture Banks, and Foreign Banks. The analysis technique used is multiple regression analysis. Because the data used is secondary data, to determine the accuracy of the model, it is necessary to test several classical assumptions that underlie the regression model. Classical assumption tests used in this study include tests, normality, multicollinearity, heteroscedasticity and autocorrelation. Furthermore, to test the effect of financial ratios as mentioned, statistical tests withused Multiple Linear Regression were. Based on the research, it is found that the Capital Ratio, Operational Efficiency, Interest Yield, Liquidity, and Non-Performing Loans affect bank profits.